2004
DOI: 10.1097/01.rli.0000100892.87214.49
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cerebrospinal Fluid and Blood Dynamics in Healthy Volunteers and Patients with Communicating Hydrocephalus

Abstract: Venous vessel compression and/or changes in intracranial subarachnoid CSF flow produce an increase in ventricular CSF flush that compensates for vascular brain expansion in patients with CH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
156
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 28 publications
19
156
3
3
Order By: Relevance
“…5 However, the principal driving forces of CSF pulsation and the transmission mechanism of the force from the blood vessels or brain parenchyma are not fully understood. Evaluation of normal CSF circulation in terms of peak velocity, flow rate, and flow velocity waveform in conjunction with evaluation of spatial blood flow may provide a useful knowledge base for diagnosing patients with disorders of CSF dynamics, such as hydrocephalus, 6,7 Chiari I malformation, 8,9 and arachnoid cysts.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the principal driving forces of CSF pulsation and the transmission mechanism of the force from the blood vessels or brain parenchyma are not fully understood. Evaluation of normal CSF circulation in terms of peak velocity, flow rate, and flow velocity waveform in conjunction with evaluation of spatial blood flow may provide a useful knowledge base for diagnosing patients with disorders of CSF dynamics, such as hydrocephalus, 6,7 Chiari I malformation, 8,9 and arachnoid cysts.…”
Section: Introductionmentioning
confidence: 99%
“…If so, then corresponding secondary abnormalities in the flow of CSF through the cerebral aqueduct (earlier onset and reduced duration of the systolic CSF flow peak) should be observable by MRI. In previous studies, phase-contrast (PC) MRI measurement of blood and CSF flow was used to investigate the mechanical properties of brain parenchyma (21,22) and to detect variations in flow due to communicating hydrocephalus (23,24). If such changes are detectable in patients with MVA, they could provide a valuable quantitative biomarker of the severity of MVA, which would be of particular use in the development and testing of novel therapeutic agents that target the cerebral vasculature.…”
mentioning
confidence: 99%
“…For example, Greitz 15 found, along with an increased aqueductal flow rate, a corresponding decreased flow rate through the craniocervical junction. Balédent et al, 12 in a larger study, found no such changes. To use stroke volume to diagnose hyperdynamic CSF, a measurement that some investigators have advocated for diagnosing shunt-responsive NPH, 19 one must first determine a baseline stroke volume in healthy elderly patients.…”
Section: Quantitative Measurements From Pcmentioning
confidence: 77%
“…One such study revealed a shorter systolic flow period of the temporal waveform for patients with communicating hydrocephalus compared with healthy controls. 12 PC measurements of CSF flow have also been used to study patients with Chiari I malformation. In these studies, the CSF flow at the craniocervical junction has been shown to exhibit changes in flow patterns, including local flow jets and bidirectional flow.…”
Section: Quantitative Measurements From Pcmentioning
confidence: 99%